Indigenous Bacillus biodiversity from plastic-contaminated soil and its potential for low-density polyethylene (LDPE) biodegradation - WAHYU IRAWATI; SERGIO TRISON LIE; GEOFFREY DARRIEN FIDELI; BILLY YOSUA COTANTIN PONGAJOW; JUANDY JO (Society for Indonesian Biodiversity, 2026)
Abstract. Irawati W, Lie ST, Fideli GD, Pongajow BYC, Jo J. 2026. Indigenous Bacillus biodiversity from plastic-contaminated soil and its potential for low-density polyethylene (LDPE) biodegradation. Biodiversitas 27 (5): d270528. https://doi.org/10.13057/biodiv/d270528. Increasing plastic use has led to persistent accumulation of low-density polyethylene (LDPE) in terrestrial environments. This study isolated and characterized indigenous Bacillus-like bacteria from plastic-contaminated soil in the public parking area of Universitas Pelita Harapan and evaluated their capacity to induce early-stage LDPE modification. Soil suspensions were plated on King’s B agar supplemented with polyethylene glycol (PEG), yielding eight morphologically distinct isolates. LDPE strips were incubated for 30 days in minimal salt medium (MSM) inoculated with each isolate, with LDPE as the principal experimental substrate and no additional organic carbon intentionally supplied. Surface changes were assessed by scanning electron microscopy (SEM), chemical changes by Fourier-transform infrared (FTIR) spectroscopy and carbonyl index (CI) calculation, and taxonomic identity by 16S rRNA gene sequencing. All eight isolates were Gram-positive, catalase-positive, endospore-forming rods, and 16S analysis assigned them to Bacillus velezensis, Bacillus altitudinis, Bacillus licheniformis, Bacillus subtilis, and Bacillus paralicheniformis. SEM revealed isolate-specific colonization-associated surface changes, ranging from roughening and small pits to deep cracks and perforation, with A.4.I.1 showing the most extensive damage. FTIR spectra indicated oxidation-related changes, including intensified carbonyl and C-O bands; screening-level CI values ranged from 0.190 to 0.346, again highest for A.4.I.1. These findings suggest that plastic-impacted urban soil can serve as a reservoir of LDPE-associated Bacillus isolates and identify B. velezensis A.4.I.1 as a priority candidate for follow-up biodegradation studies. Because FTIR/CI observations were exploratory and no mass-loss or mineralization endpoints were measured, the results should be interpreted as evidence of biodeterioration and early oxidative modification rather than complete LDPE biodegradation.